Longitudinal trajectories of peer relations in children with specific language impairment. (11th January 2014) - Mok, Pearl L. H.; Pickles, Andrew; Durkin, Kevin; Conti‐Ramsden, Gina
<x xml:space="preserve">Abstract</x> Background Peer relations is a vulnerable area of functioning in children with specific language impairment (SLI), but little is known about the developmental trajectories of individuals. Methods Peer problems were investigated over a 9‐year period (from 7 to 16 years of age) in 171 children with a history of SLI. Discrete factor growth modelling was used to chart developmental trajectories. Multinomial logistic regression analysis was conducted to investigate factors associated with group membership. Results Four distinct developmental trajectories were identified: low‐level/no problems in peer relations (22.2% of participants), childhood‐limited problems (12.3%), childhood‐onset persistent problems (39.2%) and adolescent‐onset problems (26.3%). Risk of poor trajectories of peer relations was greater for those children with pragmatic language difficulties. Prosocial behaviour was the factor most strongly associated with trajectory group membership. Overall, the more prosocial children with better pragmatic language skills and lower levels of emotional problems had less difficulty in developing peer relations. Conclusions Analysis of developmental trajectories enriches our understanding of social development. A sizeable minority in the present sample sustained positive relations through childhood and adolescence, and others overcame early difficulties to achieve low levels of problems by their early teens; the majority, however, showed childhood‐onset persistent or adolescent‐onset problems.